2014
DOI: 10.1007/s00436-014-3965-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural characteristics and molecular identification of Entamoeba suis isolated from pigs with hemorrhagic colitis: implications for pathogenicity

Abstract: Protozoan parasites of the genus Entamoeba infect many classes of vertebrates and are primarily classified based on morphological criteria. To date, only a few species have been proven to cause disease. Here, we examined the pathology of infected pigs with hemorrhage and detected Entamoeba parasites. Isolates were characterized genetically and ultrastructurally to identify the species. Histopathologically, bleeding and thrombus formation were seen only in the large intestine mucosa, where a large number of tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…It is noteworthy that Entamoeba suis was not detected. A study of five pigs taken from a population of 148 displaying hemorrhagic colitis symptoms in Japan suggested that E. suis was responsible for the disease (Matsubayashi et al 2014). Conversely, E. suis was detected in 28 specimens taken from pigs in Vietnam and no ill health was reported (Clark et al 2006).…”
Section: Entamoeba In Pigsmentioning
confidence: 99%
“…It is noteworthy that Entamoeba suis was not detected. A study of five pigs taken from a population of 148 displaying hemorrhagic colitis symptoms in Japan suggested that E. suis was responsible for the disease (Matsubayashi et al 2014). Conversely, E. suis was detected in 28 specimens taken from pigs in Vietnam and no ill health was reported (Clark et al 2006).…”
Section: Entamoeba In Pigsmentioning
confidence: 99%
“…Entamoeba trophozoites were found in the lumen and/or intestinal lesions in 53/206 (25.7%) pigs from 28/53 (52.8%) farms. The trophozoites were morphologically distinguished as E. suis-like (with the cytoplasm containing one nucleus and ingested host red blood cells visible as small dark bodies) (Matsubayashi et al 2014) or E. polecki-like (with the cytoplasm containing one nucleus and some vacuoles) (Matsubayashi et al 2015a(Matsubayashi et al , 2015b(Matsubayashi et al , 2016. Most of the pigs with trophozoites were approximately 60 days old (average: 60.8 days; median: 60.0 days).…”
Section: Clinical and Subclinical Entamoeba Infections And Tissue Dismentioning
confidence: 99%
“…The following primers were used: EhL-EhR multiplex primer sets targeting the SSU rRNA gene of E. histolytica (or EdL-EdR for E. dispar) (Evangelopoulos et al 2000), 764-RD3 and 764-765 for nested PCR detection of E. suis (Clark et al 2006), and Epolec F6-R6 primers to distinguish among E. polecki subtypes (Matsubayashi et al 2015b). DNA from a human isolate of E. histolytica (unpublished) and from E. suis and E. polecki isolates previously reported by Matsubayashi et al (2014Matsubayashi et al ( , 2015aMatsubayashi et al ( , 2015b) was used as a positive control.…”
Section: Molecular Identification Of Entamoeba Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies about gut eukaryotes conducted in pigs (Sus scrofa domesticus) used a limited sample size and mainly focused on isolated members of the eukaryote communities or parasite identification under pathogenic conditions Matsubayashi et al 2014;Shieban 1971;Summers et al 2019;White et al 2019;Wylezich et al 2019). In swine, Kazachstania spp.…”
Section: Introductionmentioning
confidence: 99%